Examining the role of EGR1 during viral infections - Woodson, Caitlin M.; Kehn-Hall, Kylene (Frontiers in Microbiology, 2022)
Early growth response 1 (EGR1) is a multifunctional mammalian transcription factor capable of both enhancing and/or inhibiting gene expression. EGR1 can be activated by a wide array of stimuli such as exposure to growth factors, cytokines, apoptosis, and various cellular stress states including viral infections by both DNA and RNA viruses. Following induction, EGR1 functions as a convergence point for numerous specialized signaling cascades and couples short-term extracellular signals to influence transcriptional regulation of genes required to initiate the appropriate biological response. The role of EGR1 has been extensively studied in both physiological and pathological conditions of the adult nervous system where it is readily expressed in various regions of the brain and is critical for neuronal plasticity and the formation of memories. In addition to its involvement in neuropsychiatric disorders, EGR1 has also been widely examined in the field of cancer where it plays paradoxical roles as a tumor suppressor gene or oncogene. EGR1 is also associated with multiple viral infections such as Venezuelan equine encephalitis virus (VEEV), Kaposi’s sarcoma-associated herpesvirus (KSHV), herpes simplex virus 1 (HSV-1), human polyomavirus JC virus (JCV), human immunodeficiency virus (HIV), and Epstein-Barr virus (EBV). In this review, we examine EGR1 and its role(s) during viral infections. First, we provide an overview of EGR1 in terms of its structure, other family members, and a brief overview of its roles in non-viral disease states. We also review upstream regulators of EGR1 and downstream factors impacted by EGR1. Then, we extensively examine EGR1 and its roles, both direct and indirect, in regulating replication of DNA and RNA viruses.